A study on the production system of Gene's garment industry. - Quesada, Joy Ofiaza; Dizon, Angelita M. (1993.)
The study was an attempt to know the production systems of Gene's Garment Industry. Specifically, the study sought to know the product line, process description, operation capacity, quality control, fare-casting, production planning, scheduling, inventory control and warehouse department. The purpose of the study was to make an analysis of the production system of the company, determine the areas for possible improvement and increase efficiency and productivity of the company. Data were collected by documenting the present system of Gene's Garment Industry. Ocular inspections were conducted in the sewing, cutting, finishing and warehouse sections. Interviews with the key personnels and workers in the production process were also conducted. The results revealed six problem areas in the plant: (1) organizational structure, (2) plant lay-out, (3) methods in the production floor, (4) quality control, (5) maintenance program, and (6) inventory control system. After a thorough analysis of the various results and areas for improvement, the management's lack of provision of properly designed equipments and supervision was pinpointed as the main general problem. The researcher concluded that the company needed to introduce changes in its management system. Though part of the recommendations were sort term solutions for the different results in the different areas for improvement, the concept of Total Quality Management (TQM) was included as a major recommendation to establish a holistic and systematic approach in solving its problems.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Garment industry--Philippines.